The Public Demand for a Dengue Fever Vaccine: A Contingent Valuation Survey in Phnom Penh, Cambodia - Khon, Seyhak; Seenprachawong, Udomsak (International Journal of Economics and Financial Issues, 2020)
Our study estimates the willingness to pay (WTP) for the dengue fever vaccination program at a national level in Cambodia. A double bounded format with an open-ended question was used in this study to estimate the WTP. The contingent valuation method (CVM) scenario was created as a one-year dengue fever vaccination program. Two vaccine levels were used, one with 40% and another with 80% effectiveness, neither with any side effects. Three doses were required for full protection. We used a 600-split sample survey in Phnom Penh, Cambodia of those aged 20 to 60 years old and with Cambodian nationality. Subjects were asked how much they would be willing to pay for dengue fever vaccination via a one-time income tax surcharge of either 50,000, 150,000, 200,000, 350,000, 500,000, or 600,000 riel, respectively. As shown by the Tobit Model, the mean of households’ willingness to pay to support the dengue fever vaccination program were 98,841 riel and 149,124 riel for the 40% and 80% levels, respectively. Income, gender, marital status and education had a positive relationship with households’ WTP, while occupation had a negative relationship. Keywords: Contingent Valuation Method, Dengue Fever Vaccine, Willingness to Pay (WTP) JEL Classifications: I11, I12, I13, I15, I18 DOI: https://doi.org/10.32479/ijefi.10426